Strengthening Pancasila and Rahmatan Lil Alamin Profiles Through Wayang-Based Learning: A Study on Enhancing Students' Spiritual and Social Attitudes at MA Plus Al Muhibbin - Ummu Farhatin; Sri Minarti; Ari Abi Aufa; Hidayatulloh (Institut Attanwir Bojonegoro, 2026)
This study explores the implementation of the Project to Strengthen the Pancasila Student Profile and Rahmatan Lil Alamin Student Profile based on wayang media to enhance students' spiritual and social attitudes at MA Plus Al Muhibbin Jatirogo Tuban. The Merdeka curriculum allows students to choose activities freely according to their interests, and this Project incorporates local culture through wayang media. By participating in a wayang kulit performance, students are expected to develop key character traits, such as faith, devotion, independence, tolerance, and cooperation. The study employs a qualitative case study approach to assess the Project's implementation in the school setting. Data collection involved direct observation, interviews with teachers and students, and documentation of the activities. The data were analyzed descriptively and qualitatively to evaluate the impact of wayang media on students' spiritual and social attitudes. The results showed that this Project improved students' discipline, devotion to worship, and active participation in school activities. Students exhibited stronger adherence to the values of Pancasila and Rahmatan Lil Alamin, as evidenced by their enhanced spiritual and social attitudes. These changes were particularly evident during the Fastabin event, the school's annual festival, where students showcased their talents. This study concludes that wayang media is an effective tool in strengthening students' character and enhancing their spiritual and social identity, aligned with the Merdeka curriculum